Systematic identification and expression profiling of calmodulin-binding transcription activator genes reveal insights into their functional diversity against pathogens in sugarcane - Talha Javed; Wenzhi Wang; Juan Li; Tingting Sun; Linbo Shen; San-Ji Gao; Shuzhen Zhang (Plant Stress)
The calmodulin-binding transcription activator (CAMTA) proteins in plants play significant roles in signal-transduction, activation of regulatory networks, and defense response against environmental stressors. In this study we systematically identified a total 17 CAMTA genes (named as SsnpCAMTAs) in Saccharum spontaneum Np-X genome. Moreover, SsnpCAMTAs exhibited diverse physio-chemical and gene structural attributes. Notably, eight SsnpCAMTA gene pairs displayed segmental duplication events, while CAMTA genes from S. spontaneum Np-X and Arabidopsis thaliana shared homology relationship. In-vitro interaction networking showed that SsnpCAMTA1 and SsnpCAMTA2 were the core protein which interacted with each other as well as with other four different proteins (SsnpCAMTA5/7/13/17). To check functional variability, the expression profiles of SsnpCAMTAs were quantified in transcriptomic and proteomic datasets triggered by Xanthomonas albilineans (Xa) and Acidovorax avenae subsp. avenae (Aaa). The temporal expression of SsnpCAMTA4/5 was ranged between 1.7–3.5 folds in sugarcane cultivars triggered by Xa infection. Most of the SsnpCAMTAs exhibited irregular expression profile in sugarcane cultivars triggered by Aaa infection. Additionally, transcript expression profiles of eight candidate genes SsnpCAMTA1/2/5/7/8/12/13/17 were determined by RT-qPCR assay in sugarcane cultivars Zhongtang3 (resistant to smut) and ROC22 (susceptible to smut) under Sporisorium scitamineum pathogen infection. Interestingly, the transcript expression of SsnpCAMTA5 was upregulated from 1.4 to 10.8 folds as compared to control in both cultivars, while SsnpCAMTA8 was downregulated in both cultivars. Overall, our results provide valuable candidate gene resources for the development of disease-resistant sugarcane cultivars in the face of current climate change scenarios.